Still we rise : a love letter to the Southern biscuit with over 70 sweet and savory recipes - Council, Erika (Clarkson Potter/Publishers, 2023)
"A love letter to the Southern biscuit, honoring its place in Black culinary culture and beyond with over 50 delicious recipes and a striking story to tell. Part cookbook, part cultural history, part memoir, Still We Rise is a tribute to the glories of flour, butter, and buttermilk baked tall, tender, and flaky. Erika Council is the founder and head baker of the renowned Bomb Biscuit Company in Atlanta, Georgia. The granddaughter of legendary soul food chef Mildred (Mama Dip) Council, a teacher and activist who cooked and baked to support the civil rights movement, Erika knows all about the power of the persistent biscuit. Here, recipes connect readers to the traditions and stories of the South and to the people who instilled in her a love of bread making, including her grandmothers and mother, family friends, and acquaintances, along with her favorite Black cookbook authors of the past 100 years who inspired some of her biscuit creations. Through over fifty unique recipes, both sweet and savory, like Corn Milk Biscuits, Cheerwine Mustard, Red Curry Basil Biscuits, Hominy Honey Butter and a Fried Oyster Biscuit Sandwich (plus a mind-blowing Cinnamon Sugar and Pecan Biscuit), Erika takes us on a journey through Black resilience, excellence, and heritage in the American South with delicious and accessible recipes"--